Internal Jugular Venous Pseudoaneurysm in a Patient with Heart Failure and Severe Tricuspid Regurgitation - Sujoy Phookan; Patrick T. Strickland; Bishoy Hanna; Gregory R. Hartlage; Ankit Parikh; Stephen D. Clements (Case Reports in Vascular Medicine)
The differential diagnosis of a lateral neck mass includes a number of possible etiologies. While jugular venous aneurysms and pseudoaneurysms are rare entities, they should be considered in the differential diagnosis of a pulsatile lateral neck mass. We present a case of an idiopathic jugular venous pseudoaneurysm and its association with worsening tricuspid regurgitation in a patient with heart failure with preserved ejection fraction.